Comparative analysis of minimally invasive approaches for gallbladder and common bile duct stones: combined endoscopic techniques vs. ERCP with laparoscopic cholecystectomy - Fang, Haixing; Chen, Wenchao; Wu, Zhengrong; Ding, Guoping (Frontiers in Surgery, 2025)
ObjectivesThe combined technology of laparoscopy, choledochoscope and gastroscope was used in the treatment of gallbladder stones combined with common bile duct stones, which consists of laparoscopic cholecystectomy (LC), laparoscopic common bile duct exploration with primary closure (LCBDE-PC) and combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage (GC-NBD). The clinical effects of the combined technology were evaluated based on hospital stay, hospital costs, postoperative complications, recurrence of stones, and overall patient satisfaction.MethodsFrom July 2017 to December 2020, 206 patients with gallbladder stones combined with common bile duct stones were reviewed retrospectively. According to the surgical method, the patients were divided into Triple-Scope group (LC + LCBDE-PC + GC-NBD), (n = 38), ERCP + LC group [endoscopic retrograde cholangiopancreatography (ERCP) followed by LC], (n = 96) and T tube group (LC + LCBDE + T tube drainage), (n = 72). The differences in stone size, hospital stay, hospital cost, postoperative gallstone recurrence rate and postoperative complications were compared among three groups.ResultsNo postoperative bile leak occurred in Triple-Scope group, and patients were discharged successfully, and the abdominal drain was removed around 3 days after surgery, and the nasobiliary drainage was removed around 5 days after surgery with a hospital stay of 9.5 ± 2.65 days. The length of hospital stay and hospital cost in the Triple-Scope group were lower than those in the ERCP + LC group (P < 0.01), but not significantly different from those in the T tube group (P > 0.05). The diameter of common bile duct and stone size were significantly larger in the Triple-Scope group and T-tube group than in the ERCP + LC group (P = 0.001; P = 0.004), and the recurrence rate of stones in the Triple-Scope group was not significantly different compared with those in the other two groups (P = 0.43).ConclusionsFor patients with gallbladder stones combined with common bile duct stones, the triple-scope combination is safe and effective with fast recovery, and it is worthy of clinical promotion and application.